2018
DOI: 10.1186/s12711-018-0392-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective advantage of implementing optimal contributions selection and timescales for the convergence of long-term genetic contributions

Abstract: BackgroundOptimal contributions selection (OCS) provides animal breeders with a framework for maximising genetic gain for a predefined rate of inbreeding. Simulation studies have indicated that the source of the selective advantage of OCS is derived from breeding decisions being more closely aligned with estimates of Mendelian sampling terms () of selection candidates, rather than estimated breeding values (EBV). This study represents the first attempt to assess the source of the selective advantage provided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…König et al (2010) demonstrated the benefits of OCS compared to truncation selection in two commercial White Leghorn lines and one experimental line in the context of conventional selection. The advantage of OCS over truncation selection is in optimizing contributions, which are a function of animal Mendelian sampling terms (Woolliams et al, 2015; Howard et al, 2018). This means that OCS and genomic selection work in synergy (Daetwyler et al, 2007; Maltecca et al, 2020; Sonesson et al, 2012; Obšteter et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…König et al (2010) demonstrated the benefits of OCS compared to truncation selection in two commercial White Leghorn lines and one experimental line in the context of conventional selection. The advantage of OCS over truncation selection is in optimizing contributions, which are a function of animal Mendelian sampling terms (Woolliams et al, 2015; Howard et al, 2018). This means that OCS and genomic selection work in synergy (Daetwyler et al, 2007; Maltecca et al, 2020; Sonesson et al, 2012; Obšteter et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“… König et al (2010) demonstrated the benefits of OCS compared to truncation selection in two commercial White Leghorn lines and one experimental line in the context of conventional selection. The advantage of OCS over truncation selection is in optimizing contributions, which are a function of animal Mendelian sampling terms ( Woolliams et al, 2015 ; Howard et al, 2018 ). This means that OCS and genomic selection work in synergy ( Daetwyler et al, 2007 ; Sonesson et al, 2012 ; Obšteter et al, 2019 ; Maltecca et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mean of the selection criterion weighted by the optimised contributions is a measure of future genetic mean, while group coancestry weighted by the optimised contributions is a measure of future group coancestry. The advantage of OCS over truncation selection is its emphasis on managing between and within family (Mendelian sampling) variation ( Howard et al, 2018 ). The usefulness of OCS in conventional layer breeding programs was presented by König et al (2010) .…”
Section: Introductionmentioning
confidence: 99%
“…This shows the importance of proper base population specification (including unknown parent groups) for meaningful partitioning. This long-term dynamic of contributions is related to the dynamics of “long-term genetic contributions” in the context of genetic gain and inbreeding [ 12 , 13 ], but it should be noted that the “long-term genetic contributions” are trait agnostic (depend only on the pedigree). On a related note, with the implemented method in AlphaPart, we can evaluate (long-term) genetic contributions by setting breeding values to 1 for all animals and partitioning the breeding values by paths [ 6 ].…”
Section: Discussionmentioning
confidence: 99%